2015
DOI: 10.1039/c4cp05235h
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of alcohols with the calcite surface

Abstract: A clearer understanding of calcite interactions with organic molecules would contribute to a range of fields including harnessing the secrets of biomineralisation where organisms produce hard parts, increasing oil production from spent reservoirs, remediating contaminated soils and drinking water aquifers and improving manufacturing methods for industrial products such as pigments, soft abrasives, building materials and optical devices. Biomineralisation by some species of blue green algae produces beautifully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 26 publications
4
44
1
Order By: Relevance
“…Moreover, the adsorption onto calcite by IPA molecules is expected to be lower than that by ethanol, because of steric effects. Similarly, the coverage of calcite surface was found to be lower for t-butanol (having CH3 groups protruding laterally, hence taking more space) compared to ethanol [45]. This is expected to allow for an increased reactivity of the calcite surface in the water-IPA system, compared to the water-ethanol system, as well as for an increased reactivity of the ions in the solution.…”
Section: Effect Of Alcohol Typementioning
confidence: 98%
“…Moreover, the adsorption onto calcite by IPA molecules is expected to be lower than that by ethanol, because of steric effects. Similarly, the coverage of calcite surface was found to be lower for t-butanol (having CH3 groups protruding laterally, hence taking more space) compared to ethanol [45]. This is expected to allow for an increased reactivity of the calcite surface in the water-IPA system, compared to the water-ethanol system, as well as for an increased reactivity of the ions in the solution.…”
Section: Effect Of Alcohol Typementioning
confidence: 98%
“…It was found that alcohols heavier than methanol (including ethanol) tend to bind to the calcite surface more strongly than water and acetic acid (31). Very recently, the interactions of a series of alcohols with the calcite surface were studied using X-ray photoelectron spectroscopy coupled with MD simulation, in which all alcohols were found to bond with calcite surface through the hydroxyl group forming closely packed, ordered monolayer (33). All these previous investigations suggest a spatially thin gap with low ethanol density between the first adsorbed monolayer and the bulk alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…For calcite and alumina, the ethanol molecules mainly orient themselves perpendicular to the surface. [78][79][80][81]83 Although for Al(OH) 3 the preferred orientation is either around 0°or 60−70°8 2 and for FeOOH it is between 30−60°, 82 we find a clear preference for the ethanol molecules to align parallel to the surface.…”
Section: ■ Resultsmentioning
confidence: 77%